An examination of national climate policy integration at the local level of development in Ghana. Issue 3 (4th March 2023) - Adzei, Francis Anderson; Alornu, Mawusi Adzo
ABSTRACT: This paper assessed the extent to which local government authorities have mainstreamed climate change adaptation strategies in their development policies in selected districts in Ghana, using a qualitative case study design within the phenomenological epistemology. Forty-four respondents participated in this study from the decentralised departments of local authorities key informant interviews (KIIs) were used for data collection in the study areas. The study findings revealed that climate policy integration at the study districts was done as a compliance measure rather than a response to real needs of the districts. A gaping chasm therefore exists between stated and actual climate change-related goals. Lack of collaboration, weak coordination of sector plans and weak community and private sector engagement were identified as the causal factors of the gap between the rhetoric and reality of integrating climate change concerns into district development plans in the study areas. Further, competing local priorities on the district agenda, institutional capacity constraints and information and technological constraints were identified as major barriers for the local authorities in adaptation to climate change. It is concluded that although climate change and its related policies have been integrated into the various national development policies, climate policy integration remains a challenge at the district level.